2015
DOI: 10.1007/s10646-015-1580-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of extremely acidic cyanide-laced mining waste

Abstract: With respect to acidic, cyanide-laced tailings, the data about in situ toxicity and biological activity in highly polluted environment are often lacking. The aim of this study was to assess the microbial characteristics, composition of oribatid mite species, and level of genotoxic impact on plants in the area of inactive tailings pond (Horná Ves, Kremnica region). Sampling of the tailings, soils and selected plant species was carried out in spring of 2012. Trace element analysis (inductively coupled plasma emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Relatively low values of the basal respiration of microorganisms (up to 31 μg/g of substrate) in all our samples were definitely caused by the high contents of potentially toxic elements. Such contents of metals resulted in decreasing of carbon dioxide production by microorganisms ( Feketeová et al., 2016 ). Several authors ( Yuangen et al., 2006 , Zhang et al., 2015 ) suggest soil microbial indicators such as microbial biomass and basal respiration to be useful indicators of polluted environment.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively low values of the basal respiration of microorganisms (up to 31 μg/g of substrate) in all our samples were definitely caused by the high contents of potentially toxic elements. Such contents of metals resulted in decreasing of carbon dioxide production by microorganisms ( Feketeová et al., 2016 ). Several authors ( Yuangen et al., 2006 , Zhang et al., 2015 ) suggest soil microbial indicators such as microbial biomass and basal respiration to be useful indicators of polluted environment.…”
Section: Resultsmentioning
confidence: 99%
“…These results were demonstrated by canonical correspondence analysis of the association between mite abundance and the environmental factors. Specialist studies have revealed that, in heavy metal polluted soils, the number of bacteria, Actinomycetes and fungi does not decrease, suggesting that such microorganisms may resist increased or even toxic concentrations of heavy metals, and thus constitute a food source for decomposer oribatids 27,70 . On the other hand, soil pH and humidity are correlated with vegetation cover, affecting local habitat conditions for C. bicultrata, G. obvia and L. neerlandica , as well as for Tectocepheus velatus and Diapterobates oblongus 71 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest classification, the mites (Acari), can be divided into two superorders: Parasitiformes (with orders: Opilioacarida, Holothyrida, Ixodida and Mesostigmata) and Acariformes (with orders: Trombidiformes and Sarcoptiformes- suborder Oribatida) 21 . Mite species of the Mesostigmata (mainly predators) and Oribatida (decomposers) groups are sensitive to disturbance such as mining activities 22–27 .…”
Section: Introductionmentioning
confidence: 99%
“…Мы полагаем, что обработка азотобактерией семян горчицы, как сидерального растения, может быть использована на практике для улучшения биогенности корнеобитаемой толщи санитарно-защитных насаждений. Вместе с тем, не исключена возможность формирования биогенной массы с участием почвоулучшителей, как традиционных, так и альтернативных [43,44,45]. Такие подходы позволят ускорить биологическую активность и трофические взаимоотношения в корнеобитаемом слое биоконсервантов.…”
Section: рис 2 морфометрические данные ростков овса и горчицы на отходах обогащения железных руд: адлина (в мм); б -воздушно-сухая масса unclassified
“…Несмотря на отсутствие растительного покрова на их поверхности, они не безжизненны. На отходах обогащения сульфидных руд Уральского региона развиваются железоокисляющие, серо-и пирит-окисляющие микроорганизмы, а также сульфатредуцирующие и ацидотолерантные гетеротрофные бактерии и мик-ромицеты [37], на отходах обогащения железной руды в районе Курской магнитной аномалиимикробные деструкторы органического вещества [26], на отходах цианирования в Западной Сибириазотобактерии [5], на кислых отходах цианирования в Словакиипочвенные бактерии и орибатиды-панцирные клещи [43]. На поверхности хвостов обогащения полиметаллических и железных руд Кузбасса и в биогенно неразвитых эмбриозёмах Кузбасса присутствуют несовершенные микромицетыплесневые грибы и азотобактерии, продуценты гумусоподобных веществ.…”
Section: Introductionunclassified